2010
DOI: 10.1027/1016-9040/a000003
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Stress and Poor Health

Abstract: This paper investigated whether the lack of social connectedness, as measured by the subjective feeling of loneliness, mediates the well-known relationship between interpersonal stress and psychological distress. Furthermore, a relationship between interpersonal stress and somatic symptoms was hypothesized. The study sample included 3,268 women and 3,220 men in Western Norway. The main findings were that interpersonal stress was significantly related to psychological distress as well as to somatic symptoms, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Mette, Maurice, & John pointed out that interpersonal stress was significantly correlated with mental pain, somatic symptoms, while social networking can moderate the relationship between interpersonal stress and psychological distress [32]. Individuals with high levels of social anxiety tend to expect negative evaluation by others in interpersonal situations, and are therefore likely to interpret neutral evaluation as negative evaluation, and consequently to worry about this [33].…”
Section: Intercorrelations Of All Variables In the Studymentioning
confidence: 99%
“…Mette, Maurice, & John pointed out that interpersonal stress was significantly correlated with mental pain, somatic symptoms, while social networking can moderate the relationship between interpersonal stress and psychological distress [32]. Individuals with high levels of social anxiety tend to expect negative evaluation by others in interpersonal situations, and are therefore likely to interpret neutral evaluation as negative evaluation, and consequently to worry about this [33].…”
Section: Intercorrelations Of All Variables In the Studymentioning
confidence: 99%
“…The authors hypothesized that an individual's health outcomes are intertwined with their stress levels and social environments. The study also found that individuals with lower levels of stress experienced stronger social connectedness and increased physical activity (Aanes et al, 2010).…”
mentioning
confidence: 67%
“…The cut points for stress management measure were determined by the distribution of the data. Interpersonal relationships involve using communication to achieve a sense of intimacy and closeness in meaningful relationships with others (Aanes et al, 2010). Communication involves sharing thoughts and feelings through verbal and nonverbal messages (Aanes et al, 2010).…”
Section: Dependent Variables/outcomesmentioning
confidence: 99%
“…Stress can, in turn, result in increased feelings of loneliness (Aanes et al 2010, 2011). As a consequence of stress associated with the experience of having a parent with health limitations, children may have an increased need and desire for a supportive social network.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%